Meat Productivity Of Karakul Rams Of Different Colors - Bekbaev K. A; Ansatbayev P.A; Ajiniyazov B. K. (Zien Journals, 2025)
The article presents the study of milk productivity of karakul sheep depending on the colour in the northern conditions of the Republic of Karakalpakstan. Optimal opportunities of increasing мeat productivity were determined; the results of changing daily milk productivity in agedependent dynamics weregiven
Keywords: Milk Productivity; Sheep Colour; Sheep Age